A ground current suppression method for systems with a large number of photovoltaic (PV) inverters - Wenping Zhang; Wenping Zhang; Donghui Li; Yiming Wang; Po Xu; Baosong Liu (Frontiers in Energy Research)
In large PV plants, a large number of PV inverters are linked together at grid-side to generate more power. However, as the number of PV inverter modules increases, the ground current problem worsens. This can result in a ground current fault, and cause the inverter failed and disconnected from the grid. In this paper, the solutions, including hardware and software, are proposed to suppress the ground current. The hardware solution is to connect filter capacitors back to the DC-bus, directing more ground current to the inverter rather than the grid to reduce the ground current. Additionally, the software solutions, including carrier phase shifting and carrier frequency shifting, are proposed. In the software solutions, the ground current for PV inverters can be cancelled each other, which can alleviate the ground current problem. In the paper, the system architecture is presented first. The concept of connecting the neutral point of the filter capacitors to the DC-bus midpoint is explained. The zero-sequence mathematical model is then built. Moreover, the effect of the zero-sequence voltages of the DC/AC converter and the grid on the zero-sequence current is investigated. Then, the hardware solution is explained. The control architecture is presented, followed by an explanation of how to obtain the three-phase output voltage and zero-sequence components for PV inverters. Two software solutions, including carrier phase shifting and carrier frequency shifting, are detailed. Finally, the experiment is conducted to verify the theory.